(untitled) (Al-Qamar, 2021)
The objective of the current study is to compare the perceptions of two important segments i.e. Islamic bankers and Islamic scholars concerning the financing products provided by Islamic banks, to assess their basis whether financing products are trade-based or interest-based. It examines difference in general perception, generic underlying mechanism of offered products, and suggestive measures regarding Islamic banking products. Data was collected from Islamic bankers and Islamic scholars using a self-administrated structured questionnaire. Data of 200 respondents was analyzed using descriptive statistics, reliability, and paired sample t –test. Results indicate a considerable difference between bankers and scholars view for Islamic banking products in terms of general perception, generic underlying mechanism of offered products, and suggestive measures.